(untitled) (Medical Forum Monthly, 2021)
Objective: To find out frequency and outcomes of undiagnosed diabetes mellitus in patients presenting with acute ST elevation myocardial infarction (STEMI). Study Design: Descriptive / Cross- Sectional Study Place and Duration of study: This study was conducted at the Cardiology Department, Lady Reading Hospital, Peshawar from November 2018 to May 2019. Materials and Methods: Patient of either gender having age ranging between 30-75 years old with acute STEMI who present within 12 hours of symptoms and with no past history of documented diabetes mellitus were included in the study. Venous blood samples for laboratory data, including random blood sugar, two fasting blood sugar and HBA1c using hitachi modular evo p800 machine was done. Results: A total of 158 patients having acute STEMI were studied. Males were 68.4% (n=108).The mean age was 59.65 ±10.80 years. Frequency of undiagnosed diabetes mellitus was 31.64 % (n = 50). In non-diabetics stress hyperglycemia was found in 51.85 % (n=56) patients. Among various types of STEMI, anterior STEMI was more common presentation 34.1 % (n=54. p= 0.85). Mean HBA1C was 6.19 ± 1.87%. Frequency of Ventricular tachycardia (VT) was 22.2 % in which undiagnosed diabetics were n=18 (p=0.004).Ventricular fibrillation was present in 13.3 % patients with undiagnosed diabetics were n=14 (p=0.001). Frequency of AF was 13.9% (n=22) with undiagnosed diabetics having AF in n=13 (p=0.003). SVT was present in 5.7% (n=9) patients with not significant difference between two groups (p=0.017). Among various mechanical complications VSR was present in 10 % (n=16) of patients (p=0.001), cardiogenic shock in 11.1 % (n=18) patients (p=0.004), acute LVF was present in 15.8 % patients (p=0.017). Conclusion: In our study we concluded that one third of patients having acute ST elevation myocardial infarction have undiagnosed diabetes mellitus (31.64 %, n = 50). The most common complication was ventricular tachycardia among electrical complication and LVF among mechanical complication.